Integrated Learning Models: An Overview of Learning Ecosystems in High Schools in Indonesia - Nugroho, Mohamad Setio; Akmal, Suriati; Pawenang, Supawi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This article was created to explain the design of an integrated learning model by considering the learning ecosystem to be implemented in secondary schools in Indonesia. The novelty of this article is an overview of the learning ecosystem that integrates micro and macro aspects. Micro aspects to represent the managerial conditions of educational institutions, consist of three variables, namely priority of management, individual readiness, and technological support. The macro aspect is represented by Educational Policies which are national education policies. These variables were analyzed to see their effect on the learning outcome. The respondents of this research are teachers who are members of the Subject Teachers' Consultation (MGMP) Surakarta City, Indonesia, totaling 289 people, consisting of 156 women (53.98%), and 133 men. (46.02%). Withdrawal of sample data is done by quota random sampling technique. The use of this quota random sampling technique is to determine the representation of each region so that the results will be able to represent reality. The research was conducted from March 2019- September 2022 in Surakarta, Indonesia. The analysis technique of this research uses SEM (Structural Equation Model). The results of the study show that educational policies significantly affect priority of management and learning outcomes. Priority of management significantly affects individual rediness and technological support. Priority of Management does not significantly affect learning outcomes. Technological support significantly affects learning outcomes. Individual readiness does not significantly affect learning outcomes. All indicator variables significantly affect the construct. Keywords: priority of management, individual readiness, technological support, educational policies, learning outcomes.